Disruption of Foveal Space Impairs Discrimination of Peripheral Objects - Weldon, Kimberly B.; Rich, Anina N.; Woolgar, Alexandra; Williams, Mark A. (Frontiers in Psychology, 2016)
Visual space is retinotopically mapped such that peripheral objects are processed in a cortical region outside the region that represents central vision. Despite this well-known fact, neuroimaging studies have found information about peripheral objects in the foveal confluence, the cortical region representing the fovea. Further, this information is behaviorally relevant: disrupting the foveal confluence using transcranial magnetic stimulation impairs discrimination of peripheral objects at time-points consistent with a disruption of feedback. If the foveal confluence receives feedback of information about peripheral objects to boost vision, there should be behavioral consequences of this phenomenon. Here, we tested the effect of foveal distractors at different stimulus onset asynchronies (SOAs) on discrimination of peripheral targets. Participants performed a discrimination task on target objects presented in the periphery while fixating centrally. A visual distractor presented at the fovea ~100ms after presentation of the targets disrupted performance more than a central distractor presented at other SOAs. This was specific to a central distractor; a peripheral distractor at the same time point did not have the same effect. These results are consistent with the claim that foveal retinotopic cortex is recruited for extra-foveal perception. This study describes a new paradigm for investigating the nature of the foveal feedback phenomenon and demonstrates the importance of this feedback in peripheral vision.